Fluorosed fibroblast attachment on fluorosed and nonfluorosed teeth after SRP and EDTA root biomodification - Neha Girotra; K L Vandana (Wolters Kluwer Medknow Publications, 2014)
Background: Fluorosis causes mineralization changes in the tooth and can lead to morphologic alterations of fibroblasts. To understand the effect of fluorosis on periodontal healing, the initial step during healing, such as fibroblast attachment to the root surface, needs to be evaluated. Hence, the objective of the present study was to study the attachment of fluorosed fibroblasts on the fluorosed and nonfluorosed root fragments. Materials and Methods: A total of 56 fluorosed and nonfluorosed, periodontally healthy and diseased tooth roots were obtained and allotted to eight groups: Fluorosed and nonfluorosed healthy controls (FH and NFH, respectively), fluorosed and nonfluorosed diseased controls (FD and NFD, respectively), fluorosed and nonfluorosed roots treated with scaling and root planing (FD + S and NFD + S, respectively), and similar groups treated with scaling and root planing and 24% ethylenediaminetetraacetic acid (EDTA) gel application for 2 min (FD + SE and NFD + SE, respectively). After the respective treatment, the root fragments were incubated in the human periodontal ligament fibroblast cells obtained and cultured from freshly extracted healthy human fluorosed premolar tooth root. Results: In the nonfluorosed roots category, greater attachment was found in the untreated nonfluorosed diseased (P = 0.036) and SRP-treated nonfluorosed diseased groups (P = 0.008) as compared to the nonfluorosed healthy group. While in the fluorosed roots category, no significant difference was observed in FL-FA (P > 0.05) within the group. However, no attachment was observed in EDTA-treated fluorosed root fragments. When fluorosed groups were compared to nonfluorosed groups, no significant changes were noted between the groups. Conclusion: SRP proves to be a standard requirement for fibroblast attachment to occur both in fluorosed and nonfluorosed roots. Although there was no significant difference in attachment between SRP and SRP + EDTA among fluorosed roots, EDTA does not seem to be a promising agent for root biomodification in fluorosed roots in a given concentration and time of treatment.